2008
DOI: 10.1111/j.1744-9987.2008.00560.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Hepatitis B Vaccine Immunity in Hemodialysis Patients

Abstract: Although the efficacy of hepatitis B vaccines in patients undergoing chronic hemodialysis (HD) treatment has been documented, the persistence of immunity in this population remains largely unknown. In this study we evaluated the persistence of hepatitis B vaccine immunity in HD patients. We followed 37 hepatitis B vaccinated HD patients (following a four-dose vaccination schedule of 40 mug injections intramuscularly in the deltoid muscle at 0, 1, 2, and 6 months) for up to one year to evaluate the persistence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…Studies in hemodialysis patients have shown that an anti-HBs concentration of X100 mIU/ml after vaccination is necessary to maintain protective antibody concentrations for 1 year after vaccination and to reduce the need for additional booster doses. [24][25][26] Indeed, this cutoff is considered to be the best surrogate marker of long-term seroprotection in immunocompromized patients by a number of vaccination advisory bodies. 27,28 The higher proportion of subjects achieving anti-HBs antibody concentrations of X100 mIU/ml after primary vaccination with the HB-AS04 vaccine compared with a conventional recombinant HBV vaccine has been shown to translate into a reduced need for a booster dose over long-term follow-up (up to 42 months).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in hemodialysis patients have shown that an anti-HBs concentration of X100 mIU/ml after vaccination is necessary to maintain protective antibody concentrations for 1 year after vaccination and to reduce the need for additional booster doses. [24][25][26] Indeed, this cutoff is considered to be the best surrogate marker of long-term seroprotection in immunocompromized patients by a number of vaccination advisory bodies. 27,28 The higher proportion of subjects achieving anti-HBs antibody concentrations of X100 mIU/ml after primary vaccination with the HB-AS04 vaccine compared with a conventional recombinant HBV vaccine has been shown to translate into a reduced need for a booster dose over long-term follow-up (up to 42 months).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in hemodialysis patients have shown anti-HBs antibody concentrations ≥100 mIU/ml following vaccination to be predictive of long-term persistence of circulating antibodies. [12][13][14] Indeed, this cut-off is considered to be the best surrogate marker of long-term seroprotection in immunocompromised patients by a number of vaccination advisory bodies. 15,16 Results of an earlier study of the HB-AS02 vaccine in a smaller group of healthy volunteers also found all subjects to be seroprotected after two vaccine doses.…”
Section: Discussionmentioning
confidence: 99%
“…Further randomized and long lasting studies are needed whether three doses are as effective as four doses. Until then, 4 doses of vaccination will be suitable in these patients as suggested (2, 3). …”
mentioning
confidence: 99%